Evaluating the Performance of Three Chambers Microbial Salinity Cell (MSC) Subjected to Different Substrate Concentrations to Accomplish Simultaneous Organic and Salt Removal in the Wastewater - Rustiana Yuliasni; Nur Zen; Nanik Indah Setianingsih (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2020)
This study aimed to identify the effect of substrate concentration on the performance of A Three chambers Microbial Salinity Cell (a three chambers MSC). In this study, 3 three chambers MSC was made of plexy glass with total volume of 200 ml. Alumunium wrapped with with platinum on vulcan carbon cloth were used as electrodes,with each working area 63 cm2. The results showed that a Three chambers Microbial Salinity Cell was able to generate electricity and at the same time removed salinity. The degree of electricity deneration and salinity removal were influenced by initial substrate concentration in the anode chamber. The higher substrate concentration, the better performance of MSC. The best performance of MSC achieved when COD was 2034 mg/L, resulted in maximum voltage of 0. 44 V, and maximum current density of 0.29 mA/m2. With % CE was 5.4%. The maximum conductivity increase in salinity chamber was from 11.2 µS/cm to 1027 µS/cm (salinity 0.57% ppt)